2013
DOI: 10.1093/abbs/gmt010
|View full text |Cite
|
Sign up to set email alerts
|

Klf7 modulates the differentiation and proliferation of chicken preadipocyte

Abstract: Krüppel-like factor 7 (Klf7) has been extensively studied in the mammalian species, but its function in avian species is unclear. The objective of this study was to reveal the function of chicken Klf7 (Gallus gallus Klf7, gKlf7) in adipogenesis. The results of real-time reverse transcription polymerase chain reaction demonstrated that the relative mRNA level of chicken Klf7 (gKlf7/gβ-Actin) in the abdominal adipose tissue was significantly associated with the abdominal fat content and the age of broilers (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 24 publications
9
58
0
Order By: Relevance
“…14,16,18) Our previous study indicated that one member of KLFs, KLF7, is expressed in chicken adipose tissues, and plays a negative role in the regulation of chicken adipogenesis. 13,19) In the current study, the results showed that KLF3, an another member of KLFs, was also expressed in chicken adipose tissue. In addition, the sequence alignment showed that KLF3 protein is highly conserved among chicken, mouse and human, suggesting that KLF3 may have a similar function in these species (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…14,16,18) Our previous study indicated that one member of KLFs, KLF7, is expressed in chicken adipose tissues, and plays a negative role in the regulation of chicken adipogenesis. 13,19) In the current study, the results showed that KLF3, an another member of KLFs, was also expressed in chicken adipose tissue. In addition, the sequence alignment showed that KLF3 protein is highly conserved among chicken, mouse and human, suggesting that KLF3 may have a similar function in these species (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…DF-1 chicken embryo fibroblast cell line (kindly provided by the Harbin Veterinary Research Institute, Harbin, China) and chicken preadipocytes, which were isolated according to the procedure previously described, 13) were grown in DMEM/F12 medium (Invitrogen), supplemented with 10% fetal calf serum (Invitrogen), and plated in 12-well dishes. In transfection assays, a fixed amount of total DNA (1 μg) was transfected in each well using the Fu-GENE HD transfection reagent (Roche).…”
Section: Klf3 Cloning and Vector Constructionmentioning
confidence: 99%
“…To date, several studies have shown that PPAR γ and C/EBP α (Yu et al 2014), as well as FATP1 (Qi et al 2013) and Klf7 (Zhang et al 2013) regulate the differentiation of preadipocytes in the chicken. However, to our knowledge, investigations into the roles of lncRNAs in preadipocyte differentiation in the chicken have not yet been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent research has revealed active roles for adipocytes in fat mass regulation and nutrient homeostasis, in addition to other homeostatic processes (Trayhurn 2005;Rosen and Spiegelman 2006). Functional studies across a variety of species show that KLF7 inhibits preadipocyte differentiation (Kawamura et al 2006;Zhang et al 2013). APOC1 is associated not only with total adipose cells but also average adipocyte size (Jong et al 2001).…”
Section: The Adipocyte Cyclementioning
confidence: 99%